Environmental Challenges and Innovations in the Asia-Europe Rail Transport Corridors in the Context of the ESG Concept - ANTONOWICZ, Mirosław; MAJEWSKI, Jakub (Journal of Environmental Management and Tourism, 2025)
The aim of the publication is to assess the significance of contemporary environmental challenges that shape strategies and expectations towards long-distance rail freight transport, as well as to present solutions aimed at reducing the environmental pressure of this mode of transport. The proposed objective and the subject of the analysis indicate that the basic research method used for the purposes of this article should be a literature review, including primarily documents that define objectives in the field of environmental protection and confrontation with programs and projects implemented in railway companies involved in the organization of long-distance rail transport on the Asia-Europe-Asia routes. The study is based on selected, detailed case studies. A marketing concept for sustainable transport development is also presented. It has been shown that innovative technologies and growing consumers’ environmental demands are increasingly responsible for the development of the modern economy. New technologies and solutions not only become part of the attractiveness and competitiveness of transport logistics chains, but also contribute to reducing their environmental impact, thanks to application of the concept of sustainable marketing. The subject of rail freight traffic between Asia and Europe is analyzed in the paper in the specific context of the ESG concept, with a valuable contribution of the unique materials of various railway entities, including the Organization for Co-Operation between Railways, illustrating state-of-the-art environmental solutions in Eurasian transport corridors.